Critical pedagogy and race in TESOL - Ammar Tekin (Institut Parahikma Indonesia, 2020)
Having been initiated by the work of Paolo Freire in Brazil and other South American countries, critical pedagogy has continued to influence the English language teaching profession since the 1980s. Focusing on social change and social justice via education, critical pedagogy views education as a political activity. On the edges of the spectrum, education can maintain the status quo or challenge the social, political, economic, and cultural structures locally and globally. In this regard, language becomes a crucial element in maintaining or challenging the status quo. In English language teaching, the development of the field is directly related to colonialism and recently to globalism. Through its aims and content, English language teaching needs to be critically evaluated in terms of the values being transmitted in schools, training centres, textbook, media, and so on. Moreover, although learning the English language is a global phenomenon, especially textbooks used in language teaching continues to marginalise various races, with a colour blindless mentality. Critical multiculturalism can be an organic response to this distorted perspective, whether it is made consciously or unconsciously.